Hubungan Antara Food Coping Strategi dan Ketahanan Pangan Rumah Tangga Miskin di Wilayah Pesisir, Hutan Tropis dan Perkotaan Provinsi Kalimantan Timur: Hubungan Antara Food Coping Strategi dan Ketahanan Pangan Rumah Tangga Miskin di Wilayah Pesisir, Hutan Tropis dan Perkotaan Provinsi Kalimantan Timur - Aryatika, Karera; Pijaryani, Indria; Wahyuni, Leny Eka Tyas (Amerta Nutrition, 2026)
Background: Food security remains a major challenge for low-income households, especially in geographically and socioeconomically diverse regions such as tropical forests, coastal areas, and urban settings. Food coping strategies are crucial mechanisms used by households to address food insecurity. Objectives: This study aims to examine the relationship between food coping strategies and food security among low-income households in coastal, tropical forest, and urban areas of East Kalimantan Province, Indonesia. Methods: A cross-sectional quantitative study was conducted in three regions: Samarinda City (urban), Muara Badak (coastal), and Muara Wahau (tropical forest). Respondents were selected using simple random sampling. Data were collected using structured questionnaires on socio-demographics, food coping strategies (RCSI), and food security status (US-HFSSM). Statistical analyses included chi-square tests, t-tests, ANOVA, and correlation analysis. Results : The majority of households in tropical forest areas demonstrated high coping strategies (72.5%) and good food security (82.4%). Coastal households had the lowest coping capabilities (56.4%) and the highest rate of food insecurity (50%). In urban areas, 44.3% of households remained food insecure despite better access to food markets. Conclusions:There is a significant relationship between food coping strategies and food security, particularly in tropical forest and urban areas. Households in tropical forests benefit from local natural resources and traditional knowledge, enhancing their food security. In contrast, coastal and urban areas require targeted interventions to strengthen adaptive capacities and food access among low-income households.